2016
DOI: 10.1111/hepr.12746
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis progression predicts survival in patients with primary biliary cirrhosis

Abstract: Aim:The prognosis and natural history of primary biliary cirrhosis (PBC) has improved, and the clinical end-point for PBC needs to be discovered. We aimed to identify surrogate markers for predicting long-term prognosis in patients with PBC.Methods: A total of 106 patients were divided into 53 responders and 53 non-responders based on the median rate (69%) of decrease in γ-glutamyl transpeptidase levels at 1 year after initiating ursodeoxycholic acid therapy. We aimed to identify the differences between ursode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Treatment with ursodeoxycholic acid (UDCA) reportedly improves the prognosis of patients with PBC and produces an optimal biochemical response to UDCA . We have recently reported that a decrease in γ‐glutamyl transpeptidase (GGT) levels from baseline by >69% at 1 year after the initiation of UDCA treatment is predictive of the risk of developing end‐stage liver disease in patients with PBC (Nara definition) . Patients who have been treated with UDCA at an early histological stage of PBC have a similar life expectancy to the general population, and only a few will ever develop cirrhosis .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment with ursodeoxycholic acid (UDCA) reportedly improves the prognosis of patients with PBC and produces an optimal biochemical response to UDCA . We have recently reported that a decrease in γ‐glutamyl transpeptidase (GGT) levels from baseline by >69% at 1 year after the initiation of UDCA treatment is predictive of the risk of developing end‐stage liver disease in patients with PBC (Nara definition) . Patients who have been treated with UDCA at an early histological stage of PBC have a similar life expectancy to the general population, and only a few will ever develop cirrhosis .…”
Section: Introductionmentioning
confidence: 99%
“…proposed a new histological staging system to evaluate PBC progression that takes into account histological heterogeneity . Long‐term prognosis is predicted by portal‐bridging fibrosis based on either the Scheuer or Nakanuma staging systems . Several studies have reported that UDCA treatment delays fibrosis progression of paired liver biopsies in patients with PBC in the early histological stages .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The G protein-coupled Mas receptor has been recognized as the main receptor for angiotensin (1)(2)(3)(4)(5)(6)(7). Binding of angiotensin (1)(2)(3)(4)(5)(6)(7) to Mas activates a counter-regulatory pathway with antifibrotic, anti-inflammatory, and vasodilatory effects. 65 Cultured activated human HSCs have been shown to express RAS components and synthesize angiotensin II, 67 which has been proposed to be a trigger for the profibrogenic mediator CTGF.…”
Section: Mediators Of Myofibroblast Precursor Cell Activationmentioning
confidence: 99%